Representação de linhas de transmissão trifásicas diretamente no domínio das fases por meio da matriz ABCD - Souza Junior, Newton Vieira de [UNESP] (2015)
This work presents a transmission line model developed directly in the domain of phases from representation through quadripolos for polyphase lines. Thus, the line model was structured as function of longitudinal and transverse parameters variable frequency and by means of ABCD matrix. This approach was possible from the implicit use of a transformation matrix, variable a function of frequency used in transformations between domains of the phases and modes. The transformation matrix is explicitly described as a function of the longitudinal and transverse parameters of a three-phase line. Modal line magnitudes were converted into the domain of the phases, resulting in an analytical model developed directly in the domain phase. The proposed model was applied to simulate a three-phase line without a vertical symmetry plane and also situations involving asymmetric unbalanced load conditions, for example: phase-to-phase or phase-ground and unbalanced loads. The simulations considering asymmetrical or unbalanced conditions are not possible in many models in the time domain and frequency using a real and constant matrix. However, from the implicit use of variable frequency transformation matrix, the model was able to simulate electromagnetic transients in asymmetrical manner and unbalanced. One of the major attributes of the model consists of the inclusion and non-linear simulation conditions in a simplified manner by means of boundary conditions applied to the input and output signals of ABCD matrices. The simulations in the time domain and frequency domain were made during the development of this work, enabling the comprehensive analysis of possible applications the lines proposed transmission model